Identifikasi Model Faktor Kesuksesan Proyek Pengembangan Sistem Informasi - Handrie Noprisson (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
To facilitate the business needs of information systems development between software engineers and clients, perspectives on information systems processes and for software engineers are essential. Therefore, factors influencing project development to implement technology need to be identified and evaluated. This study aims to propose tentative theories about the determinants of success and principles in the development of information systems projects. The strategy in this systematic literature review is based on PRISMA’s flow chart which consists of four steps of identification, screening, feasibility, and selection of included data. The success factors of an information systems development project include people, projects, and organizations. These factors play an important role in determining the success of such projects. People, including project teams and leadership, are important to ensure effective communication, project team capabilities, and competencies. The project should have clear specifications and well-defined goals and objectives. The organization must be committed and involved throughout the project. In addition, factors related to the knowledge and expertise of the organization are also important for the success of the project. Overall, the success of an information systems development project depends on the collaboration and coordination of people, effective project management, and organizational support and involvement.